(untitled) (International Journal of Engineering and Computer Science, 2018)
This paper introduces a real world learning ideas to teach the concept of data structure among the students effectively. Data structure has been the area of research for a long time in the area of technology. The need to understand the concept of data structure is thereby important not only for the students but also for the researchers.